ANALISIS TINGKAT KEPUASAN NASABAH TERHADAP PELAYANAN BANK SUMSEL BABEL CABANG SUNGAILIAT - Fikri, Zakiyudin; Angela, Inggit Tria; Muslim, Dhady (Universitas Panca Marga, 2023)
The purpose of this study was to see the level of customer satisfaction with the quality of service provided by Bank Sumsel Babel Sungailiat Branch. The research method uses a quantitative type. Data collection techniques using questionnaires or surveys. The results showed that the level of customer satisfaction with the services provided by the Sumsel Babel bank was in the very satisfied category. This can be proven by the results of respondents' responses to each indicator used in measuring the level of service. Respondents' responses to each indicator gave a positive response. The conclusion is that the customer satisfaction level of Bank Sumsel Babel Sungailiat Branch is already in the very satisfied category, although there are still a small number of customers who state that on several indicators, they give dissatisfied responses. But overall, it is covered by dominant responses in the very satisfied category according to the majority of customers. Recommendations to the management of Bank Sumsel Sungailiat Branch to continue to maintain and improve the quality of services that have been obtained so that they can be able to compete with bank companies that are already large and trusted